Determinação de tamanhos de nanopartículas de FexOy utilizando técnicas de caracterização estrutural e magnética - Jesus, Jônathas Rafael de (2015)
In this work we have studied the effects caused by the insertion of the sucrose on the structural and magnetic properties of iron oxides prepared by co-precipitation and hydrothermal synthesis. Results of X-ray diffraction (XRD) allied to Rietveld refinement indicate the formation of hematite (a-Fe2O3) and magnetite (Fe3O4) compounds with average particle size about 3 to 10 nm. Transmission electron microscopy (TEM) images of Fe3O4 samples present spherical-like shape with particles sizes in good agreement with those estimated by XRD. The magnetization measured as function of magnetic field (MvsH) and temperature (MvsT) has shown that the particles present superparamagnetic behavior at room temperature. In particular, MvsH curves at low temperature (5K) for a-Fe2O3 nanoparticles exhibit a narrowing caused by possible surface effects. Furthermore, the fittings performed by using theoretical models for MvsH curves of Fe3O4 samples are discrepant with respect to the sizes obtained by other techniques, wich suggests the formation of magnetic clusters due to the presence of strong dipolar interactions that are also evidenced by the increasing blocking temperature. The control of the size distributions of the samples of a-Fe2O3 and Fe3O4 were more efficient when the hydrothermal synthesis was used. Moreover, all results demonstrate a strong dependence of the particles size distribution with the presence at sucrose.